Comparison of diagnostic efficacy of 18F-FDG PET/CT and 68Ga-DOTANOC PET/CT in ectopic adrenocorticotropic hormone syndrome - Zhang, Bing; He, Qiao; Long, Yali; Zhang, Yuying; Wang, Xiaoyan; Chen, Zhifeng; Liu, Jianbo; Zhang, Xiangsong (Frontiers in Endocrinology, 2022)
Purpose: Fluorine-18 (18F)-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) and gallium-68 (68Ga)-somatostatin analog (SSA) PET/CT imaging have been increasingly used in ectopic adrenocorticotropic hormone syndrome (EAS); however, the diagnostic efficacies of these two methods in patients with EAS remain unclear. Our study aimed to compare the diagnostic efficacies of 18F-FDG PET/CT and 68Ga-DOTANOC PET/CT in EAS. Methods: The clinical and imaging data of 68 patients with EAS who underwent 18F-FDG PET/CT and 68Ga-DOTANOC PET/CT examinations from December 2016 to April 2021 were analyzed retrospectively, and the diagnostic efficacies of these methods were compared. Results: In 37 cases, imaging was performed to locate the primary tumour lesion (localization group), and in 31 to evaluate tumour load or metastasis (staging group). Primary tumours were detected in 48.65% (18/37) of the localization group patients. According to scan-based analysis, the tumour lesion detection rates and false positive rates of 18F-FDG PET/CT imaging and 68Ga-DOTANOC PET/CT imaging were 18.92% vs. 45.95% (p < 0.05) and 21.62% vs. 2.70% (p < 0.05) respectively. For lesion-based analysis, the tumour lesion detection rates and false positive rates were 24.13% vs. 58.62% (p >0.05) and 31.04% vs. 3.45% (p < 0.05). In 90.32% (28/31) of the staging group patients, 286 of 292 lesions were confirmed as tumour lesions. Based on scan analysis, the detection rates and false positive rates of 18F-FDG PET/CT imaging and 68Ga-DOTANOC PET/CT imaging were 83.87% vs. 67.74% (p > 0.05) and 12.90% vs. 9.68% (p > 0.05) respectively. Based on lesion analysis, the detection rate and false positive rates were 93.84% vs. 54.80% (p < 0.05) and 1.37% vs. 1.03%(p > 0.05). Conclusion: 68Ga-DOTANOC PET/CT imaging may be more suitable than 18F-FDG PET/CT for identifying the primary tumour in patients with EAS, while 18F-FDG PET/CT may be more advantageous than 68Ga-DOTANOC PET/CT for patients with suspected metastasis.